Model Pendidikan Karakter Religius Berbasis Tripusat Pendidikan : Studi Kasus di SDN Bandulan 3 Kota Malang - Siti Khoiriyah (Medan Resource Center, 2022)
This study aims to determine the importance of forming religious character through synergy and cooperation between the three educational centers. Because a child will grow up in 3 environments, namely the family environment which can be called the main and first bench of a child's education, the school environment is a place where a child is in the process of studying and developing self-potential, and the community environment, which is a place where a child proceeds apart from at home and at school. The study method used is qualitative, and the method of presenting the data is descriptive analysis, and is designed with a literature approach that explores several discussions about education, character education, and three education centers. The results of the discussion in this study include: 1) religious character education implemented at Public Elementari School of Bandulan 3 emphasizes cooperation and synergy between the school, parents and the community, 2) the synergy of tri educational centers in growing religious character is a family effort in instilling faith as a foundation. development, efforts by schools or formal educational institutions in teaching science and culture with character as the content of development, and community efforts in providing space as development goals.